The design of electronic medical records for patients of continuous care. Issue 1 (January 2021) - He, Xiaolan; Cai, Lei; Huang, Shiju; Ma, Xiaoju; Zhou, Xueling
Abstract: In order to meet the ever-increasing needs of health care, as well as helping patients who need continuous care after being discharged from the hospital and making modern medical technology better serve humans, the design of electronic medical records for continuous care patients, especially those with malignant tumors, is investigated. In the research process, the idea of Browser/Server (B/S) framework is adopted, and the corresponding electronic medical record system is designed based on the targets and the overall structure of the system; afterward, the black-box testing and white-box testing are carried out to test the functions, reliability, and stability of the designed electronic medical record system; in addition, combined with other research results, the feasibility of the design is proved. It can be seen that the electronic medical record system designed for patients who need continuous care in the study is absolutely feasible, which can be further researched and improved with the development of electronic medical records; therefore, it would make greater contributions to both patients and hospitals in the future.